2007
DOI: 10.1002/elps.200600183
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hadamard transformation to MEKC

Abstract: The Hadamard transform (HT) technique, which permits the S/N in CE to be improved, was applied to MEKC. Multiple sample injection of fluorescent analytes according to a Hadamard code sequence was performed using an optically gated sample injection technique, in which a sample plug was produced based on photodegradation by irradiation with an intense laser beam. The capillary and reservoirs were filled with a sample solution containing buffer components and SDS as a pseudostationary phase. A preliminary study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…When using cyclodextrin (CD) as a chiral selector, FITC‐labeled glutamic acid enantiomers are clearly separated in the transformed data with enhanced S/N ratios. Furthermore, Hadamard transformation using optically gated sample introduction was applicable to the MEKC separation of amino acids . Therefore, HT‐CE with optically gated sample introduction is useful for the sensitive detection of FITC‐labeled analytes with no degradation of resolution in the separations.…”
Section: Hadamard Transform Cementioning
confidence: 99%
“…When using cyclodextrin (CD) as a chiral selector, FITC‐labeled glutamic acid enantiomers are clearly separated in the transformed data with enhanced S/N ratios. Furthermore, Hadamard transformation using optically gated sample introduction was applicable to the MEKC separation of amino acids . Therefore, HT‐CE with optically gated sample introduction is useful for the sensitive detection of FITC‐labeled analytes with no degradation of resolution in the separations.…”
Section: Hadamard Transform Cementioning
confidence: 99%
“…To conclude this paragraph, we would like to mention the work by Hata et al . 82, who demonstrated the applicability to a MEKC separation of Hadamard transformation (HT), a technique that permits the S / N to be improved. A sample solution containing Phe, Glu, and Asp, labelled with FITC, was used in a demonstration of HT‐MEKC separation; 30 mM sodium borate buffer (pH 9.0) containing 30 mM SDS was the running buffer employed.…”
Section: Mekc Of Amino Acids: Application To Real Samplesmentioning
confidence: 99%
“…It has been used in conventional CE [18,19] and in microchip CE [14,17,21,22]. Hata et al have even reported using cross-correlation CE technique for MEKC analyses [23]. All cross-correlation CE experiments reported before have been done using some sort specific sample injection device that is not available in commercial equipment.…”
Section: Introductionmentioning
confidence: 96%